(untitled) (JOURNAL OF INDIAN EDUCATION, 2007)
As an apex national agency of educational reform, NCERT is expected to review the school curriculum as a regular activity, ensuring the highest standards of rigour and deliberative openness in the process. Consequently, in 2004, the NCERT initiated the review of National Curriculum Framework for School Education– 2000. In the context of this exercise, a National Steering Committee chaired by Prof. Yash Pal and 21 National Focus groups were set up. These focus groups were created to generate ideas and to reflect upon curricular areas, national concerns and systemic reforms. Each Focus Group through discussions and intensive deliberations produced a research-based Position Paper providing a comprehensive view of existing knowledge in the area and future direction. The position papers prepared by the NFGs provided inputs to the National Curriculum Framework–2005. All these position papers are available in print form and also on NCERT’s website. For the readers of the Journal of Indian Education we present here the text of one such position paper Aims of Education.